THE POTENTIAL OF METABOLITES PRODUCED BY Lactobacillus Plantarum ATCC 8014 AS A BIOPRESERVATIVES AND ANTI-BACTERIAL Materials in ANIMAL FOOD PRODUCTS - Akhmad Hidayatulloh; J. Gumilar; E. Harlia (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2019)
Lactobacillus plantarum is a probiotic-lactic acid bacteria that normally lives in the human digestive tract. These bacteria are known to produce metabolites that have inhibitory activity against pathogenic bacteria and food spoilage. Therefore, the metabolites produced by L. plantarum was potential to be used as a biopreservation for animal product, especially milk and meat. In order to obtain accurate data about the optimal production time of these metabolites and their antibacterial activity, the growth curve of L. plantarum which was incubated up to 48 hours at 37 oC and 5.0% of CO2 was observed. Observations were also made on the inhibition of gram-negative pathogenic bacteria (Escherichia coli and Salmonella typhimurium) and gram-negative (Staphylococcus aureus and Listeria monocytogenes) which are often found in meat and milk. The results showed that the metabolites produced during the incubation process can inhibit gram-negative and gram-positive pathogenic bacteria. The best production of metabolites is at the 24th hour which shows the diameter of the inhibition zone of 11.9 mm for L. monocytogenes; 11.6 mm for E. coli; 12.5 mm for S. typhimurium and 9.1 mm for S. aureus. Therefore, the production process of biopreservation for food from the results of L. plantarum's metabolism has a potential to be developed and applied to animal product, especially milk and meat.